Peningkatan Keterampilan Menulis Tulisan Argumentasi Siswa Kelas X.3 SMA Negeri 2 Kota Sungai Penuh Berbantuan Media Peta Pikiran - Ridha Hasnul Ulya; Syahrul R; Novia Juita (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: The important problem in this research is the weakness of argumentation writing skills of grade X.3 students of SMA Negeri 2 Sungai Penuh, as a result a media is needed in order to increase student’s argumentation writing skills. The purposes of this research are as follows (1) describe the increasing process of grade X.3 students of SMA Negeri 2 Sungai Penuh argumentation writing skills using Mind Mapping, and (2) describe the increasing result of grade X.3 students of SMA Negeri 2 Sungai Penuh argumentation writing skills using Mind Mapping. This research is a Classroom Action Research using analytic descriptive method. The subjects of this research are 30 grade X.3 students of SMA Negeri 2 Sungai Penuh. Based on the data analysis and the result of the research, some conclusions are made as follows. First, teaching and learning process of argumentation writing using Mind Mapping can increase student’s learning process in grade X.3 SMA Negeri 2 Sungai Penuh. Second, teaching and learning process of argumentation writing using Mind Mapping can increase student’s learning result, the students got 55,6 in pre-phase become 75 in first phase and 81,5 in the second phase. Along with these conclusions, the researcher can recommend two things, first, grade X.3 students of SMA Negeri 2 Sungai Penuh argumentation writing skills should be increase through intensive exercise. Second, the argumentation writing skills need to be grown up among students. Kata Kunci: keterampilan menulis, tulisan argumentasi, media peta pikiran